Perlindungan Hukum Bagi Kreditur Akibat Adanya Pailit yang Diajukan oleh Debitur Ditinjau dari Undang-Undang Kepailitan - Sonny Triyono Saputra (Fakultas Hukum Universitas Islam Jember, 2020)
Bankruptcy is a situation where the debtor is unable to make payments on the debts of his creditors. The state of being unable to pay is usually caused by financial distress from the debtor's business that has experienced bankruptcy. This is a way to get out of the debt problem that hides a debtor, where the debtor no longer has the ability to pay debts. the debt to its creditors. If the inability to repay debts that are due is realized by the debtor, then the step that can be taken by the debtor is by submitting a request to determine the status of bankruptcy to himself, or by determining the status of bankruptcy issued by the court if it has been proven that the debtor has indeed not been able to repay debts that are due and collectible.